ENHANCING STUDENT WRITING HABITS WITH POE AI: A STUDY ON DIGITAL TOOLS FOR ACADEMIC SUCCESS - Nasution, Bincar; Matondang, Saiful Anwar; Barus, Efendi (University of Kuningan, 2025)
The advent of advanced AI technologies has opened up new avenues for enhancing the learning process of writing. The present research investigates the potential of Poe AI as an instrument for fostering improved writing habits among students at the university level. This study employs an applied research technique approach to investigate the effectiveness of Poe AI in fostering writing skills, elevating writing quality, and reinforcing writing habits. Data were gathered through observations, interviews, and text analysis from 10 students who utilized Poe AI for a two-month duration. The findings suggest that Poe AI has the potential to be an efficacious instrument for cultivating consistent writing habits and enhancing writing quality in regard to coherence, grammar, and structure.